USP44 Stabilizes DDB2 to Facilitate Nucleotide Excision Repair and Prevent Tumors - Zhang, Ying; Mandemaker, Imke K.; Matsumoto, Syota; Foreman, Oded; Holland, Christopher P.; Lloyd, Whitney R.; Sugasawa, Kaoru; Vermeulen, Wim; Marteijn, Jurgen A.; Galardy, Paul J. (Frontiers in Cell and Developmental Biology, 2021)
Nucleotide excision repair (NER) is a pathway involved in the repair of a variety of potentially mutagenic lesions that distort the DNA double helix. The ubiquitin E3-ligase complex UV-DDB is required for the recognition and repair of UV-induced cyclobutane pyrimidine dimers (CPDs) lesions through NER. DDB2 directly binds CPDs and subsequently undergoes ubiquitination and proteasomal degradation. DDB2 must remain on damaged chromatin, however, for sufficient time to recruit and hand-off lesions to XPC, a factor essential in the assembly of downstream repair components. Here we show that the tumor suppressor USP44 directly deubiquitinates DDB2 to prevent its premature degradation and is selectively required for CPD repair. Cells lacking USP44 have impaired DDB2 accumulation on DNA lesions with subsequent defects in XPC retention. The physiological importance of this mechanism is evident in that mice lacking Usp44 are prone to tumors induced by NER lesions introduced by DMBA or UV light. These data reveal the requirement for highly regulated ubiquitin addition and removal in the recognition and repair of helix-distorting DNA damage and identify another mechanism by which USP44 protects genomic integrity and prevents tumors.